Is there an informal employment wage premium? Evidence from Tajikistan - Anita V. Staneva; G. Reza Arabsheibani (IZA Journal of Labor & Development, 2014)
This paper defines informal sector employment and decomposes the difference in earnings between formal and informal sector employees in Tajikistan for 2007. Using quantile regression decomposition technique proposed by JAE, 20:445-465, 2005 and considering self-selection of individuals into different employment types, we find a significant informal employment wage premium across the whole earnings distribution. Taking advantage of RES, 90:290-299, 2008matching approach and considering the possibility of misleading results due to different observed characteristics of formal and informal workers, we still find a wage gap in favour of informal sector workers.
Keywords: J21; J23; J24; J31; 330; Formal/informal employment; Quantile regression decomposition; Matching; Endogeneity